2013
DOI: 10.1016/j.numecd.2012.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Gazpacho consumption is associated with lower blood pressure and reduced hypertension in a high cardiovascular risk cohort. Cross-sectional study of the PREDIMED trial

Abstract: (R.M. Lamuela-Raventos). 1 On behalf of the PREDIMED Study Investigators. + MODELPlease cite this article in press as: Medina-Remón A, et al., Gazpacho consumption is associated with lower blood pressure and reduced hypertension in a high cardiovascular risk cohort. Abstract Background and aim: Hypertension is a major public health problem and a leading cause of death and disability in both developed and developing countries, affecting onequarter of the world's adult population. Our aim was to evaluate whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 31 publications
0
3
1
Order By: Relevance
“…38 In the PREDIMED trial, patients who consumed high amounts of Gazpacho, a phytochemical-rich vegetable soup, had lower SBP (−2.6 mm Hg, P o0.05), DBP (−1.9 mm Hg, P o 0.05) levels and the risk of HTN in these subjects was also lower (OR = 0.73 (95% CI: 0.55-0.98)) than nonconsumers; it has been suggested that phytochemicals in vegetable components used for preparation of Gazpacho had a synergistic effect on attenuation of blood pressure. 39 In the present study, there was no association between HTN and major phytochemical-rich food groups alone, but dietary PI was inversely associated with HTN occurrence. There is insufficient evidence regarding whether the phytochemical content of different foods has synergistic effects or interaction in the mixed diets.…”
Section: Discussioncontrasting
confidence: 62%
“…38 In the PREDIMED trial, patients who consumed high amounts of Gazpacho, a phytochemical-rich vegetable soup, had lower SBP (−2.6 mm Hg, P o0.05), DBP (−1.9 mm Hg, P o 0.05) levels and the risk of HTN in these subjects was also lower (OR = 0.73 (95% CI: 0.55-0.98)) than nonconsumers; it has been suggested that phytochemicals in vegetable components used for preparation of Gazpacho had a synergistic effect on attenuation of blood pressure. 39 In the present study, there was no association between HTN and major phytochemical-rich food groups alone, but dietary PI was inversely associated with HTN occurrence. There is insufficient evidence regarding whether the phytochemical content of different foods has synergistic effects or interaction in the mixed diets.…”
Section: Discussioncontrasting
confidence: 62%
“…The antioxidant effects of MeDiet observed in plasma could contribute to reduce the prevalence of hypertension in patients with MetS. In fact, the consumption of key foods included in the MeDiet was inversely associated with systolic and diastolic blood pressure and the prevalence of hypertension in a previous PREDIMED cross‐sectional assessment in another subset of the PREDIME trial . Similarly, it has been pointed out that following a MeDiet is inversely associated with the clustering of hypertension, diabetes, obesity, and hypercholesterolemia among high‐risk patients .…”
Section: Discussionmentioning
confidence: 99%
“…Several cross-sectional studies evaluated the relationship between vegetable intake and CVD risks [ 26 , 51 , 52 ]. It was found that total cholesterol (TC), the TC/high density lipoprotein cholesterol (HDL-C) ratio, and hemoglobin A1c were significantly improved in women who consumed more than 10 servings/week of tomato-based food products compared to those consuming fewer than 1.5 servings/week [ 51 ].…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…These results suggested a potential effect of potato consumption on CVDs, as high fasting blood glucose, low serum HDL, and diabetes are recognized as CVD risk factors. Furthermore, it was indicated in a cross-sectional study with 3995 Mediterranean participants at high CVD risk that gazpacho (a Mediterranean vegetable-based cold soup that contains plenty of phytochemicals) intake was negatively correlated with hypertension [ 52 ]. It was found that both the systolic and diastolic blood pressure of the participants reduced with means of −1.9 mm Hg (95% CI: −3.4 to −0.6) and −2.6 mm Hg (95%CI: −4.2 to −1.0) and of −1.5 mm Hg (CI: −2.3 to −0.6) and −1.9 mm Hg (95% CI: −2.8 to −1.1), respectively, in moderate (1 to 19 g/day) and high (more than 20 g/day) gazpacho intake categories, compared with the control group.…”
Section: Epidemiological Studiesmentioning
confidence: 99%